Device Features and/or Personality Traits? Disentangling the Determinants of Smartphone Nomophobia and Pathology among Urban Millennials - Saidon, Janiffa; Musa, Rosidah; Hashim, Hairulnizam; Atory, Nurul Ainun Ahmad; Md Sohid, Faizah; Mohd Yusof, Nuryusmawati; Syed Omar, Syed Ashrene (Information Management and Business Review, 2023)
Smartphones have emerged as a mobile device that provides users with "smart" functionalities, aesthetics features and capabilities. These smart devices are the “must have” advanced communication tools and have been assimilated as an integral part of the everyday life. Although academic scholars and practitioners have started to venture into a research stream that focuses on behavioral models to elucidate and predict smartphone consumption trends and behavior, however, there is limited empirical research that attempts to unleash factors that triggered smartphone users to become nomophobia (no mobile phone phobia) and consecutively in turn become pathology (also known as addiction or dependency) user. Henceforth, this work seeks to explore both emerging phenomena by developing and validating a research model which is based on the Media Dependency Theory. The structural equation modelling analysis was conducted using Smart Partial Least Square (SmartPLS3) procedure with a dataset of 272 smartphone users who belong to the urban Millennials generational cohort. Two main predictors are hypothesized, which are the smartphone features (software and hardware) and users’ personality traits (openness, neuroticism, and extraversion). The results suggest that multiple facets of smartphone users’ personalities, particularly neuroticism significantly cause the smartphone users to become nomophobia and subsequently pathological. Whereas, the device hardware features have a positive significance effect on nomophobia, nevertheless not trigger pathology. Surprisingly, software features of the smartphone do not offer evidence of their effect on nomophobia as well as pathology. The key findings uncovered from this exploratory research provide rich insights for theoretical and practical implications.